PENGARUH MODEL COOPERATIVE LEARNING TIPE TWO STAY TWO STRAY TERHADAP MAHARAH KALAM KELAS VIII MTs BABUL FUTUH PANDAAN - sari, putri puspita; Hasyim, Mochamad (Lugatuna : Jurnal Prodi PBA, 2024)
The cooperative learning method, "types two stays two strays," fosters group collaboration among students, encouraging socialization, active learning, and mutual assistance to achieve educational objectives. It particularly addresses the challenge of enhancing Arabic speaking proficiency among students, making it a central focus for intensive intervention and improvement. The purpose of this study was to find out the application of the Two Stay Two Stray cooperative learning method to Maharah Kalam. and to determine the effect of the Method on Maharah Kalam class VIII MTs Babul Futuh Pandaan. The approach used by researchers in this study is a quantitative approach. The type of research used is a pre-experimental group pretest-posttest. In contrast, the research instruments used in data collection techniques are tests, interviews, and observations. From the results of the study, it was found that learning Maharah Kalam using the cooperative learning method type two stay two strays has a high significance in increasing students' mastery of maharah kalam. This is based on the final results of the paired samples test, which has a significance value of less than 0.05, namely Sig. (0.000)